2003
DOI: 10.1123/jsr.12.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 3-Minute Standing Stretch on Ankle-Dorsiflexion Range of Motion

Abstract: Context:Stretching exercise regimens are routinely prescribed to increase range of motion (ROM) and diminish injuries.Objective:To examine the effect of a 3-minute passive stretch on ankle-dorsiflexion ROM in a nonpathological population.Setting:University laboratory.Design:Prospective, randomized, controlled study.Participants:24 apparently healthy volunteers.Interventions:Subjects stood with their heels suspended from the edge of a platform. The experimental subjects stretched for 3 minutes on 3 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Results from quality assessment are presented in Table 1 . Of the studies selected for inclusion, 13 featured a control group [ 2 , 3 , 5 , 12 , 16 , 18 , 19 , 21 ],[ 23 , 25 , 29 , 31 , 32 , 38 ]. Sixteen of the included studies randomly assigned participants to treatment groups [ 1 - 3 , 5 , 12 , 14 - 16 , 18 , 19 , 21 , 23 ],[ 25 , 29 , 31 , 32 ], nine studies featured blinding of the participants, assessors or therapists [ 1 , 2 , 12 , 13 , 16 , 19 , 21 , 31 ],[ 38 ] and 13 studies reported on the reliability of the measures used [ 1 , 3 , 5 , 12 , 14 , 16 , 23 , 25 ],[ 27 , 29 - 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from quality assessment are presented in Table 1 . Of the studies selected for inclusion, 13 featured a control group [ 2 , 3 , 5 , 12 , 16 , 18 , 19 , 21 ],[ 23 , 25 , 29 , 31 , 32 , 38 ]. Sixteen of the included studies randomly assigned participants to treatment groups [ 1 - 3 , 5 , 12 , 14 - 16 , 18 , 19 , 21 , 23 ],[ 25 , 29 , 31 , 32 ], nine studies featured blinding of the participants, assessors or therapists [ 1 , 2 , 12 , 13 , 16 , 19 , 21 , 31 ],[ 38 ] and 13 studies reported on the reliability of the measures used [ 1 , 3 , 5 , 12 , 14 , 16 , 23 , 25 ],[ 27 , 29 - 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of interventions have been proposed to increase actual or functional dorsiflexion ROM at the ankle joint, including stretching, warm up and use of ultrasound [1-6,9,12-32]. Previous systematic reviews have investigated the effects of such interventions in increasing ankle joint dorsiflexion ROM in the context of ankle injuries [33] or neuromuscular disease [34].…”
Section: Introductionmentioning
confidence: 99%
“…Five trials met the inclusion criteria for the review with 161 participants (table 1). [10][11][12][13][14] Three trials were identified for inclusion in the sensitivity analyses with 118 participants. 10 11 14 No trials included participants with lower limb injuries.…”
Section: Search Resultsmentioning
confidence: 99%
“…Four of the trials ensured 100% compliance by supervising the stretches. [10][11][12][13] Youdas et al 14 used log books instead to 97 volunteers (59 women and 38 men) with mean (SD) age 27.6 (7.7) for women and 26.8 (6.9) for men. Inclusion: active ankle dorsiflexion less than 20˚.…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition to the positive effects of resistance training, stretching exercises have been shown to effectively increase ankle ROM in older adults. Gastrocnemius stretching in particular has been shown to improve ROM for individuals with limited ankle dorsiflexion [14,15]. It has been previously documented that a combination of both resistance and stretching exercises maybe an effective intervention for improving ankle mobility and postural stability in older adults [16].…”
Section: Background and Purposementioning
confidence: 99%